An Ethnography Study: The Anomaly of Post- Pandemics Technology utilization in English Learning to Gen Z students - Al Fath, Muhammad Sandy; Putri , Nikmah Sistia Eka (Universitas Ahmad Dahlan, 2023)
The presence of covid-19 has a long-lasting impact even after the pandemic is over. One of them is in the English learning process at MAN Kotawaringin Timur. The main problem raised in this study is related to changes in the learning culture of both teachers and students who display two sides, namely the positive and negative sides. The main purpose of this research is to find out the implementation, constraints, and anomalies felt by teachers related to post-pandemic learning. The research approach used is qualitative with ethnographic research type. Data collection techniques used interviews, surveys, observations, and documentation. The research subjects consisted of four English teachers. The results showed that the implementation of learning has two types of opposite ways while running the class with technology. However, both sides of perspectives had strong considerations that cannot be denied. Moreover, the anomalies are divided into three sections, the learning environment, teachers’ tendencies, and students’ misunderstanding.